ANALISIS YURIDIS PUTUSAN NOMOR 14/PDT.SUS-PHI/20201/PN.MTR TENTANG PHK BAGI PEKERJA PERJANJIAN KERJA WAKTU TERTENTU - LALU FAREZA MUAMAR FADILA; Lalu Hadi Adha (Private Law, 2023)
This recent study purposed to analyze how dispute were arranged regarding to the requests for the rights of workers who are laid off with a Fixed Time Work Agreement. Another aims of the research is also to figuring out the appropriation of legal considerations of the judges within Decision Number 14/Pdt.Sus-PHI/2021/PN.Mtr. This study uses normative legal research with statute approach and conceptual approach applied. The types and sources of legal materials used to solve the problems are primary legal materials, secondary legal materials, and tertiary legal materials. The technique/method of obtaining legal material is carried out by means of a literature study. Based on the interpretation method of analysis within the research, it is known that the dispute arrangements regarding the application for the rights of workers who were laid off with a Fixed Time Work Agreement according to labor law that if one party terminates the employment relationship before the expiration of the term, the party terminating the employment relationship is required to pay compensation to the other party as stipulated in Government Regulation Number 35 of 2001 Concerning Work Agreements for Specific Time, Outsourcing, Working Time and Rest Time, and Termination of Relations. The judge's consideration in decision No. 14/Pdt.Sus-PHI/2021/PN Mtr was rejected since the plaintiff did not appear at the trial three times in a row and had not provided evidence at trial to support the demands of his lawsuit, therefore the court was unable to fulfill the plaintiff's demands.